2021
DOI: 10.1590/1414-431x202010099
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Ureaplasma urealyticum and Mycoplasma hominis in 4082 Chinese patients

Abstract: The objective of this study was to analyze the infection rate and drug resistance of Ureaplasma urealyticum (UU) and Mycoplasma hominis (MH) in the genitourinary tract of Chinese patients. From December 2018 to June 2019, vaginal secretion or urinary secretion of outpatients in our hospital were selected for culture and drug sensitivity analysis of Ureaplasma urealyticum and Mycoplasma hominis. In 4082 Chinese samples, 1567 Mycoplasma were detected, a detection rate of 38.39%, among which 1366 cases were UU si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…When the patient's immunity was low and the patient's genitourinary environment changed, the number of mycoplasmas would increase correspondingly and achieve the effect of pathogenicity, and more reports indicate that mycoplasma infection in the genital tract will not only cause pelvic inflammatory disease, endometritis, etc., but more serious cases will induce some pathological changes leading to female infertility [14,15]. Zheng et al [16] analyzed 4082 Chinese patients infected with U. urealyticum and M. hominis, and their findings showed that the rate of Mycoplasma infection was 48.2% in women. Similar to M. hominis, Mycoplasma genitalium (M. genitalium) is also part of the normal flora, however, it is difficult to culture the organism.…”
Section: Discussionmentioning
confidence: 99%
“…When the patient's immunity was low and the patient's genitourinary environment changed, the number of mycoplasmas would increase correspondingly and achieve the effect of pathogenicity, and more reports indicate that mycoplasma infection in the genital tract will not only cause pelvic inflammatory disease, endometritis, etc., but more serious cases will induce some pathological changes leading to female infertility [14,15]. Zheng et al [16] analyzed 4082 Chinese patients infected with U. urealyticum and M. hominis, and their findings showed that the rate of Mycoplasma infection was 48.2% in women. Similar to M. hominis, Mycoplasma genitalium (M. genitalium) is also part of the normal flora, however, it is difficult to culture the organism.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in the scientific literature, reports have emerged about decrease in the sensitivity of representatives of Mycoplasmataceae family to preparations of fluoroquinolone group. Therefore, Zheng et al (2021) revealed that out of 1,567 isolates of Ureaplasma urealyticum and Mycoplasma hominis, 18.8% of the cultures were resistant to ofloxacin, 14.7% to sparfloxacin, and only 7.8% to levofloxacin. In the article by Solís-Martínez et al (2006), frequency of isolating M. hominis and U. urealyticum resistant to norfloxacin accounted for 67.8%; and 57.6% were resistant to ofloxacin.…”
Section: Discussionmentioning
confidence: 99%
“…Other virulence factors include phospholipase An and C, IgA protease, and urease. 1 It has been reported that the total infection rate of mycoplasma of 4082 patients with urogenital tract infection in China is 38.39%, mainly infected by single U. urealyticum , 2 which is inconsistent with some research results. 3 5 It suggests that there are some differences in the distribution of mycoplasma in different areas.…”
Section: Introductionmentioning
confidence: 89%
“…It has been reported that the total infection rate of mycoplasma of 4082 patients with urogenital tract infection in China is 38.39%, mainly infected by single U. urealyticum, which is inconsistent with some research results. It suggests that there are some differences in the distribution of mycoplasma in different areas. It may be related to the different levels of antibiotic use, sampling sites, detection reagents, and laboratory precision in different regions.…”
Section: Introductionmentioning
confidence: 92%